2017
DOI: 10.1080/20013078.2017.1321455
|View full text |Cite
|
Sign up to set email alerts
|

A novel community driven software for functional enrichment analysis of extracellular vesicles data

Abstract: Bioinformatics tools are imperative for the in depth analysis of heterogeneous high-throughput data. Most of the software tools are developed by specific laboratories or groups or companies wherein they are designed to perform the required analysis for the group. However, such software tools may fail to capture “what the community needs in a tool”. Here, we describe a novel community-driven approach to build a comprehensive functional enrichment analysis tool. Using the existing FunRich tool as a template, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
267
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 311 publications
(275 citation statements)
references
References 9 publications
1
267
0
1
Order By: Relevance
“…To predict the potential molecular function of miR-7116-5p, we use TargetScan, a popular bioinformatics tool to analyze 5795 predicted gene targets of miR-7116-5p, and then use Funrich software for molecular function enrichment analysis [34]. Figure 4B shows the percentage of genes predicted to be involved in molecular function of miR-7116-5p, including regulation of protein polyubiquitination, GTP binding, and ATP binding.…”
Section: Resultsmentioning
confidence: 99%
“…To predict the potential molecular function of miR-7116-5p, we use TargetScan, a popular bioinformatics tool to analyze 5795 predicted gene targets of miR-7116-5p, and then use Funrich software for molecular function enrichment analysis [34]. Figure 4B shows the percentage of genes predicted to be involved in molecular function of miR-7116-5p, including regulation of protein polyubiquitination, GTP binding, and ATP binding.…”
Section: Resultsmentioning
confidence: 99%
“…The enrichment analysis using FunRich 24 showed that exosomes from bovine colostrum samples were significantly enriched with proteins associated with the innate immune response. Proteins involved in the foremost systemic reaction-like acute phase response (APR) were highly upregulated in the colostrum samples.…”
Section: Discussionmentioning
confidence: 99%
“…Protein list of insulin‐induced and non‐induced LIM1215 EVs generated by Mascot search engine were compared based on Rsc values. Highly abundant proteins found in insulin‐induced sample (more than 2‐fold) were analysed using Cytoscape and FunRich …”
Section: Methodsmentioning
confidence: 99%